Assessment of Cereal Based Food Security Situation in Bagmati Province of Nepal: Inclusive Transformation Perspective - Paudel, R.; Nepali, P.B.; Panta , H.K.; Acharya, G.D. (Nepalese Journal of Development and Rural Studies, 2023)
This study identified the prevalence of food insecurity as per social and economic characteristics of people living in Bagmati province, thereby, giving information to plan and design the intervention appropriate and adequate enough to bring desirable changes in those areas. Food security is a complex and multidimensional concept. Measuring the concept with a single indicator is difficult due to its complexity and context specificity. This article explored the various aspects of food security in Bagmati province through primary and secondary data. This article offers a thorough analysis of different components related to food transformation systems contributing to achieve food security. It examined the food system’s numerous parts and interdependence, highlighting pressing issues and possible solutions. Encouraging women, educated and economically active youths using innovative ways would contribute improving long-term food security. Land ownership of women is directly responsible for food surplus or deficit condition of in the study area. Governments and international organizations should prioritize investment in agriculture, research and development, and infrastructure to promote sustainable and inclusive food systems.